In Vitro Anticandidal Activity Of Essential Oil Of Thymus Vulgaris - VILAS A. KAMBLE; S. D. PATIL; DEVANAND P. FULZELE (International Journal of Pharma and Bio Sciences, 2012)
The objective of the present study is to evaluate the anticandidal activity of thyme essential oil against clinical isolates of Candida species from genital fungal infections and oral thrush. Thyme oil is popularly used as antifungal treatments in aromatherapy and potent essential oil in the traditional Indian medicinal systems. Anticandidal activity of 73 clinical isolates to thyme oil and diluted thyme oil with DMSO (25%, 50% and 75%) was determined by agar disc diffusion method. Undiluted thyme oil was efficiently inhibited growth of all isolates of Candida species with growth inhibition zones ranging from 42 to 62 mm, whereas diluted thyme oil invulnerability to Candida species decreased with increased dilution rate. Minimum inhibitory concentrations (MIC) and minimum fungicidal concentrations (MFC) were evaluated by broth microdilution and broth macrodilution method. The broth microdilution assay gave MIC and MFC values ranging from 0.02–1.25 µl/ml. The broth macrodilution assay shows MIC values ranging from 0.02–0.62 µl/ml and MFC ranging from 0.04–0.62 µl/ml. The results showed that the C. krusei exhibited higher sensitivity to thyme oil than other isolates with lowest MIC of 0.02 µl/ml (v/v). The result of this study suggests that thyme oil contain potential active anticandidal components.